Importancia del licenciado en optometría en los procedimientos a seguir en el área de oftalmología del Centro de Especialidades Central Guayas IESS, Guayas-Guayaquil, octubre 2018 – abril 2019 - Guerrero Carbo, David (2019)
This thesis carries out the analysis and evaluation of the operational performance of the Graduate in Optometry in the area of Ophthalmology of the Central Guayas Health Clinic of the IESS, likewise it emphasizes the need to count on his presence for a better performance of the area, as a strategy as a means to achieve (more attention, in less time and rapid and effective diagnosis by timely delivering the report to ophthalmologists) the objectives is to streamline the ophthalmological procedures you need for your treatment and final diagnosis. These indicators were used and compared to show the relationship and difference between their presence and absence before and after making the pertinent consultations to the affiliates and managers of the area, since these indicators allow to observe the difference and the need to have their presence . The problem is posed, the general objective and the specific objectives of this thesis are established, as well as the justification, the scope and the limits of it. The data of the institution and the legal framework in which the graduate in optometry is handled are presented. As its local and global positioning in which it is already giving very good results and the reason to demonstrate in this study. The conclusions reached with the study are presented.